Stability and practical feasibility of the 3D nonlinear guidance law - Jiayi Yuan; Bowen Duan; Jianliang Ai (Scientific Reports)
Abstract In this paper, the stability of straight line tracking using the 3D version of the nonlinear guidance law in both ideal and practical scenarios is theoretically analysed. First, a more manageable state space equation is derived utilizing a trigonometric transformation. Then, a handle-friendly Lyapunov function in the sense of LaSalle is proposed. The use of this new Lyapunov function leads to a large attraction domain estimation, enabling theoretical analyses of the system stability considering the inner loop response. Moreover, based on a similar construction, an appropriate estimation model for the sampling frequency of flight data is derived.